2019
DOI: 10.3390/met9020164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure on Hydrogen Permeation in EA4T and 30CrNiMoV12 Railway Axle Steels

Abstract: A comparative study was conducted to reveal the effect of microstructure on hydrogen permeation in the EA4T and 30CrNiMoV12 railway axle steels. Unlike the EA4T with its sorbite structure, 30CrNiMoV12 steel shows a typical tempered martensitic structure, in which a large number of fine, short, rod-like, and spherical carbides are uniformly dispersed at boundaries and inside laths. More importantly, this structure possesses plentifully strong hydrogen traps, such as nanosized Cr7C3, Mo2C, VC, and V4C3, thus res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This might be correlated to the higher grain boundary density in the martensitic microstructure, as it is known that grain boundaries can be trapping sites for hydrogen [53]. However, it should be noted that the diffusion coefficient found for the ferritic SLM-ed steel is approximately two to three orders of magnitude lower than that of a typical ferritic microstructure [54][55][56]. This could be due to additional trapping sites, possibly correlated to the formation of Cu-rich precipitates during ageing (4 hours at 580°C).…”
Section: Hydrogen Permeation Behaviormentioning
confidence: 94%
“…This might be correlated to the higher grain boundary density in the martensitic microstructure, as it is known that grain boundaries can be trapping sites for hydrogen [53]. However, it should be noted that the diffusion coefficient found for the ferritic SLM-ed steel is approximately two to three orders of magnitude lower than that of a typical ferritic microstructure [54][55][56]. This could be due to additional trapping sites, possibly correlated to the formation of Cu-rich precipitates during ageing (4 hours at 580°C).…”
Section: Hydrogen Permeation Behaviormentioning
confidence: 94%
“…studies have indicated that carbides, such as nano-sized NbC, VC, and TiC, are often identified as "good irreversible straps" with high hydrogen binding energy (Eb > 60 kJ mol −1 H), decrease hydrogen diffusivity and increase critical hydrogen concentration in steel, leading to enhanced resistance to HE [26]. Therefore, reduced hydrogen damage is expected for A-1800 steel.…”
Section: Hydrogen Diffusion Behaviors and Trapsmentioning
confidence: 99%
“…The formation of carbides is directly associated with the increased carbon and the introduced micro-alloying elements (see Table 1), which also strongly improved the strength of steel to 1.8 GPa. Previous studies have indicated that carbides, such as nano-sized NbC, VC, and TiC, are often identified as "good irreversible straps" with high hydrogen binding energy (E b > 60 kJ mol −1 H), decrease hydrogen diffusivity and increase critical hydrogen concentration in steel, leading to enhanced resistance to HE [26]. Therefore, reduced hydrogen damage is expected for A-1800 steel.…”
Section: Hydrogen Diffusion Behaviors and Trapsmentioning
confidence: 99%
“…Its fatigue destruction is often accompanied by corrosion. Although the fatigue, corrosion, and hydrogen embrittlement of axle steel have been studied extensively, the interaction of these factors is rarely studied [2][3][4]. As known, corrosion fatigue starts from the active points of the material surface.…”
Section: Introductionmentioning
confidence: 99%